6(2m+3)=5(4m+2)

Simple and best practice solution for 6(2m+3)=5(4m+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2m+3)=5(4m+2) equation:


6(2m+3)=5(4m+2)

We simplify the equation to the form, which is simple to understand
6(2m+3)=5(4m+2)

Reorder the terms in parentheses
+(+12m+18)=5*(4m+2)

Remove unnecessary parentheses
+12m+18=+5+*(+4m+2+)

Reorder the terms in parentheses
+12m+18=+(+20m+10)

Remove unnecessary parentheses
+12m+18=+20m+10

We move all terms containing m to the left and all other terms to the right.
+12m-20m=+10-18

We simplify left and right side of the equation.
-8m=-8

We divide both sides of the equation by -8 to get m.
m=1

See similar equations:

| -3.2=w+(-0.2) | | 4x+66=90 | | 20=16-y/5 | | -0.10(17)+0.40x=0.05(x-6) | | 3x+18=10x-59 | | 46+3y-19=12y-9-3y | | 0.11y+0.03(y+6000)=740 | | 1.2-(-0.5)=d | | p+16=2p-4+3p | | 9x+x=3x+44 | | X+2x+3x=46 | | 5t+1/2=t+5/4+t-3/4 | | 6(7-g)=12 | | 6(7-9)=12 | | y=1.2x+4 | | x-5/3+5/3=-x/5 | | -3r(4r-8)=-36 | | 40-8x=80-10x | | 2(r+1)=18+4r | | 3.5+2x= | | -11=-9+x/6 | | 2(3-g)=4 | | 4(120000-z)+10(120000-z)=1176000 | | 8x+7=-13 | | 3x/4+7/2=17 | | 46y=5(9y-7) | | 8x+6=12+6x | | -17y+3=-25 | | 2=3+m/10 | | 2x-5/11=4-x | | 8x-2=9x+6 | | (-3x^4yz^0)(4x^0y^4z)= |

Equations solver categories